Agronomical and phytochemical investigation of Hyssopus officinalis - Galambosi, Bertalan; Svoboda, Katerina P.; Deans, Stanley G.; Hethelyi, Eva (Agricultural and Food Science, 1993)
Hyssop (Hyssopus officinalis L.) obtained from various commercial sources was grown for three years (1990-1992) in Finland. Yield characteristics, flower colour, volatile oil content/composition and its antimicrobial quality were studied. For comparison, Scottish-grown hyssop was included in oil and quality determinations. The description of the flower colour given by the seed firms was not a reliable indicator of the true colour in many cases. Oil yield was satisfactory and oil composition was rather uniform. Only one different chemotype was identified, this was derived from a Romanian seed source. There was considerable variation in herb yield between plants from different sources. The total fresh herb yield was 0.5-3.2 kg/m2, the dry leaf yield was 67-326 g/m2. Seed germination was satisfactory (76-99%), offering opportunities for seed production of varieties with different characteristics.